The Status of Implementation of Right to Education (RTE) Act, 2009 for Disadvantaged Children in Kerala - Soni, R. B. L. (JOURNAL OF INDIAN EDUCATION, 2015)
The purpose of this study was to explore the status of implementation of the Right of children to Free and Compulsory Education (RTE) Act, 2009 for disadvantaged children and children with disabilities in Kerala. Two districts (Thiruvananthapuram and Kollam) with high population of SC/ST/BPL/ children with disabilities were selected through purposive sampling. However, respondents in each category were selected using stratified random sampling. Both rural and urban schools (four in Thiruvananthapuram district and five in Kollam district) were selected. A total sample of 66 respondents was selected for this study. Since the study was of in-depth nature, responses of respondents to each item were categorised, and simple descriptive method was used in describing the results. Main findings of the study were that no information was given about SC/ST/ children with disabilities during orientation of RTE, pupil-teacher ratio is 1:50, mid-day meal consumes a lot of time because of formalities involved, children of migrant labourers from other states leave school because of inadequate arrangements for age-appropriate training for placement in different classes, weekly visit by special teacher to children with disabilities is inadequate to ensure proper learning, teachers experience difficulties in teaching different categories of children with disabilities, teachers have not been trained in the area of disabilities, and visually impaired children have not been provided teaching-learning materials individually. Thus, there is a partial implementation of RTE Act, 2009 for children with disabilities in Kerala.